PROGRAM PENJAMINAN MUTU SEKOLAH (STUDI KASUS SDN 36 DAN SDIT AL FITYAH KOTA PEKANBARU) - Suheri Suheri; Zulfan Saam; Caska Caska (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2019)
The research aims to analyze the map quality, quality manual, quality assurance and SOP institutional quality assurance SDN 36 and SDIT Al Fityah city of Pekanbaru. Informants to be interviewed in this research is the principal and Vice Principal at SDN 36 and SDIT Al Fityah city of Pekanbaru. The instruments used are shaped intervie, observation and documentation. Data analysis which is used toexpose the data quality assurance program school case studies of SDN 36 and SDIT Al Fityah city of Soweto), used a qualitative analysis. The results showed that first, map quality SDN 36 and SDIT Al Fityah city of Pekanbaru were already attempting to carry out the task of drafting the program and evaluation of the quality of education the school mapping. Second, the guideline of quality SDN 36 and SDIT Al Fityah Pekanbaru minimum service standards. Third, quality assurance SDN 36 SOP and SDITAl Fityah Pekanbaru meets the standards and infrastructure customized SNPS and SPM. Fourth, institutional quality assurance SDN 36 and SDIT Al Fityah Pekanbaru refers to the institutional structure which guarantees the quality of staffing and are handled by the head of school.